Improving Interpersonal Communication through Strengthening Personality, Emotional Intelligence, Organizational Culture, and Trust (Using the Path Analysis and SITOREM Analysis Approach in Civil Servant Teachers)) - Atmapratiwi, Heppy; Setyaningsih, Sri; Taufik, Taufik (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to improve Interpersonal Communication through strengthening Personality, Emotional Intelligence, Organizational Culture, and Trust. The research population involved civil servant teachers of Group III in public elementary schools in South Tangerang City, with a sample of 155 people selected proportionally using the Yamane formula. This research method used a quantitative approach through a survey, and the data were analyzed using Structural Equation Modeling (SEM). SITOREM analysis was also conducted to identify key variables in “Operation Research.” The results showed that Personality, Emotional Intelligence, Organizational Culture, and Trust have a significant positive influence on Interpersonal Communication. Their respective path coefficients show that Personality (βy = 0.591), Emotional Intelligence (βy2 = 0.352), Organizational Culture (βy3 = 0.134), and Trust (βy4 = 0.280) significantly influence Interpersonal Communication. In addition, Personality also has a significant effect on Trust (β41 = 0.432) and Emotional Intelligence has a significant effect on Trust (β42 = 0.492). However, Emotional Intelligence has no significant effect on Organizational Culture (β43 = 0.125), while Personality significantly affects Organizational Culture (βy2 = 0.689).